Factors influencing intrapatient variability of tacrolimus and its association with 1-year post-transplant outcomes in pediatric liver transplant recipients - Fang, Chuxuan; Dong, Chunqiang; Huang, Kaiyong; Wen, Ningyu; Chen, Yiyu; Tang, Shuangyi (Frontiers in Pharmacology, 2024)
Objective This study aims to explore the factors influencing tacrolimus intrapatient variability (TAC-IPV) and its association with 1-year post-transplant outcomes in pediatric liver transplant recipients. Methods Clinical and biological data of pediatric patients after liver transplantation were collected. The patients were divided into high- and low-IPV groups according to the median TAC-IPV for statistical comparisons. Factors with p < 0.05 in univariate analysis were introduced into binomial logistic regression analysis. Correlation analysis was used to test the connections between the Tac-IPV and outcomes within 1 year after liver transplantation (LT), and Kaplan–Meier was used to draw the survival curves. Results A total of 116 children underwent 746 measurements of TAC trough concentrations. The median TAC-IPV was 32.31% (20.81%, 46.77%). Hematocrit (p = 0.017) and concomitant medications (p = 0.001) were identified as independent influencing factors for TAC-IPV. The incidence of transplant rejection (p = 0.008), CMV infection (p < 0.001), and hospital admission due to infection (p = 0.003) were significantly higher in the high-IPV group than in the low-IPV group. Kaplan–Meier survival analysis suggests that after considering the time factor, high IPV (IPV > 32.31%) was still significantly associated with transplant rejection (HR = 3.17 and p = 0.005) and CMV infection (HR = 2.3 and p < 0.001) within 1 year after LT. Conclusion The study highlights the significant variation in TAC-IPV among children post-liver transplantation, emphasizing the impact of hematocrit levels and concomitant medications on TAC-IPV. Elevated TAC-IPV is associated with increased risks of transplant rejection, CMV infection, and readmission due to infection in the first year after liver transplantation. Close monitoring of patients with high TAC-IPV is recommended to promptly detect adverse reactions and provide timely intervention and treatment.